Designing Ultrafast Cooling Rate for Room Temperature Electrocaloric Effects by Phase‐Field Simulations. Issue 10 (14th July 2022) - Shao, Cancan; Shi, Xiaoming; Wang, Jing; Xu, Jiwen; Huang, Houbing
Abstract: Due to miniaturization and environmental friendliness, the electrocaloric effect is expected to be applied to refrigerate electronic chips and microdevices. Unlike the conventional electrocaloric effect that focuses on the temperature change, the ultrafast cooling rate is crucial to heat transport in future device units. In this work, controlling the duration of ultrafast electric field pulse on a nanosecond scale (the frequency ∼ GHz), the instant electrocaloric effect is realized in BaTiO3 and Ba(1− x ) Sr x TiO3 systems based on the modified phase‐field method. A significant ultrafast cooling rate of 10 8 K s −1 can be achieved due to the application of ultrafast electric field pulse within nanoseconds, which proved to be more efficient than the constant electric field. Furthermore, multiple electric field pulses are designed to realize the cyclic ultrafast cooling. This study provides the fundamental theoretical guidance for ultrafast cooling in solid‐state refrigeration. Abstract : Based on the dynamical phase‐field modeling method, this paper investigates the difference between electric field pulse (EFP) and conventional constant electric field and clarifies the rationality of EFP for electrocaloric refrigeration. By designing multiple EFPs, Ba0.5 Sr0.5 TiO3 can achieve an ultrafast cooling cycle at room temperature with a remarkable cooling rate up to 10 8 K s ‐1 .